P6.006 Counting the Pennies: Rational Prescribing Within the Context of the National Chlamydia Screening Programme. (13th July 2013) - Turner, K M; Horner, P; Vincent, I; Adams, E; Macleod, J
Abstract : Background: In 2010/11 the National Chlamydia Screening Programme diagnosed over 90, 000 cases of chlamydia in England. The current BASHH guidelines recommend either Azithromycin or doxycycline. Concerns have been raised questioning the efficacy of Azithromycin in routine practise. Aims: The aim of our study was to analyse whether current prescribing is in line with the criteria for rational prescribing and to estimate the cost and efficacy implications of a change in prescribing practise. Methods: We searched for published data on clinical effectiveness (both in randomised controlled trials and in practise), cost, compliance, universal use, acceptability, antimicrobial resistance and safety profiles. We developed a simple costing tool to estimate the potential cost implications of prescribing practise and clinical effectiveness on the total treatment cost and the cost per infection treated. Findings: Until 2012, Azithromycin cost £9.65 per 4-tab 250mg pack in comparison with £1.70 per 28 capsule 50mg pack (BNF 2011–12). The cost of Azithromycin is now £1.50. The most recent findings in practise have suggested that the clinical effectiveness of Doxycycline may be superior to Azithromycin. Interpretation In health economic terms, if Doxycycline is clinically superior and costs less than Azithromycin, then Doxycycline regimens dominate. This could have saved significant costs in 2011/12 (up to £500, 000). Now the costs are broadly equivalent, providing that the cheaper form of Azithromycin is prescribed. Doxycycline is also a valid choice of therapy, and extended regimens of Azithromycin could now also be considered without being prohibitively expensive. Policy recommendation Within the context of treatment of asymptomatic, uncomplicated chlamydia diagnosed through screening, Azithromycin is likely to continue to be the drug of choice. The process for implementing changes to prescription should be made more streamlined and transparent, so that evidence can be more rapidly translated into cost-savings.